2015
DOI: 10.3390/pr3020384
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Dielectric Spectroscopy and Biocalorimetry for the Monitoring of Biomass in Immobilized Mammalian Cell Cultures

Abstract: Abstract:The purpose of this study was to introduce dielectric spectroscopy and biocalorimetry as monitoring methods to follow immobilised Chinese Hamster Ovary (CHO) cell culture development. The theory behind both monitoring techniques is explained and perfusion cultures are performed in a Reaction Calorimeter (eRC1 from Mettler Toledo) as an application example. The findings of this work show that dielectric spectroscopy gives highly reliable information upon the viable cell density throughout the entire cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Near‐infrared spectroscopy has been demonstrated to be useful in monitoring metabolites, viable cell density, and total cell density in batch cultures for final product quality control (Crowley, Arnold, Wood, Harvey, & McNeil, ; Teixeira, Oliveira, Alves, & Carrondo, ). Dielectric spectroscopy has been employed to monitor the biomass in batch cultures to improve process monitoring (Ansorge, Esteban, & Schmid, ; Cole, Demont, & Marison, ; Justice et al, ; Opel, Li, & Amanullah, ). One important aspect of mammalian cell cultures for which PAT tools have been developed is the metabolically active biomass (Ansorge et al, ; Handlogten et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Near‐infrared spectroscopy has been demonstrated to be useful in monitoring metabolites, viable cell density, and total cell density in batch cultures for final product quality control (Crowley, Arnold, Wood, Harvey, & McNeil, ; Teixeira, Oliveira, Alves, & Carrondo, ). Dielectric spectroscopy has been employed to monitor the biomass in batch cultures to improve process monitoring (Ansorge, Esteban, & Schmid, ; Cole, Demont, & Marison, ; Justice et al, ; Opel, Li, & Amanullah, ). One important aspect of mammalian cell cultures for which PAT tools have been developed is the metabolically active biomass (Ansorge et al, ; Handlogten et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of dielectric properties for monitoring biomass is of interest for biopharmaceutical production as the methods are label‐free and noninvasive and have the potential to perform online analysis (Carvell & Dowd, ; Downey, Graham, Breit, & Glutting, ; Kiviharju et al, ; Lee, Carvell, Brorson, & Yoon, ; Petiot, Ansorge, Rosa‐Calatrava, & Kamen, ). It has been demonstrated that dielectric spectroscopy is a useful technique to monitor the biomass as well as the membrane and cytoplasm properties of Chinese hamster ovary (CHO) cells (Ansorge, Esteban, & Schmid, ; Ansorge et al, ; Cole et al, ; Downey et al, ; Elias, Zeiser, Bédard, & Kamen, ; Justice et al, ; Opel et al, ). Table shows the application of dielectric spectroscopy in monitoring dielectric parameters, specially cytoplasm conductivity in different cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for biopharmaceutical protein products, in particular recombinant monoclonal antibodies (mAbs), has been constantly increasing in the last decade (Walsh, ). Chinese hamster ovary (CHO) cells are the most commonly used cell lines for mAb production due to their capability of performing human‐like posttranslational modifications (PTMs; Cole, Demont, & Marison, ). Glycosylation is one of the most important PTMs for mAbs, as it impacts effector functions, pharmacokinetics, antigenicity, safety, stability, and solubility of the mAbs produced (Tharmalingam, Wu, Callahan, & T. Goudar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many concerns arise as regards to their potential toxicity to mammalian and also human cells. The following methods for studying cells characteristics were used: Raman spectroscopy [1], dielectric spectroscopy [2], and NMR spectroscopy techniques [3]. But these methods have a range of disadvantages such as relatively expensive reagents, heating and labour input.…”
Section: Introductionmentioning
confidence: 99%